Human serum albumin isoforms: Genetic and molecular aspects and functional consequences - Kragh-Hansen, Ulrich; Minchiotti, Lorenzo; Galliano, Monica; Peters, Theodore (Biochimica et biophysica acta, 2013)
At present, 67 different genetic variants of human serum albumin and proalbumin have been molecularly characterized at the protein and/or gene level. This review summarizes present knowledge about genetic and molecular aspects, functional consequences and potential uses of the variants. The frequency of bisalbuminemia in the general population is probably about 1:1000, but it can be much higher in isolated populations. Mutations are often due to hypermutable CpG dinucleotides, and in addition to single-amino acid substitutions, glycosylated variants and C-terminally modified alloalbumins have been found. Some mutants show altered stability in vivo and/or in vitro. High-affinity binding of Ni++ and Cu++ is blocked, or almost so, by amino acid changes at the N-terminus. In contrast, substitution of Leu90 and Arg242 leads to strong binding of triiodothyronine and l-thyroxine, respectively, resulting in two clinically important syndromes. Variants often have modified plasma half-lives and organ uptakes when studied in mice. Because alloalbumins do not seem to be associated with disease, they can be used as markers of migration and provide a model for study of neutral molecular evolution. They can also give valuable molecular information about albumins binding sites, antioxidant and enzymatic properties, as well as stability. Mutants with increased affinity for endogenous or exogenous ligands could be therapeutically relevant as antidotes, both for in vivo and extracorporeal treatment. Variants with modified biodistribution could be used for drug targeting. In most cases, the desired function can be further elaborated by producing site-directed, recombinant mutants. This article is part of a Special Issue entitled Serum Albumin. •67 structurally different genetic variants of albumin and proalbumin are now known.•Single-amino acid changes, glycosylations and modified C-terminal ends have been found.•Variants can have altered stability, ligand binding properties and biodistribution.•Structural changes can lead to important syndromes but apparently not to disease.•Mutants can be used as markers of migration, as antidotes and for drug targeting.